Develop your presentation skills : how to inspire and inform with clarity and confidence - Theobald, Theo, 1957- (London ; New York : Kogan Page, 2022)
"Provides step-by-step advice to prepare effectively and nail that presentation. This quick and easy guide provides a practical toolkit for developing a winning presentation and improving your confidence. Complete with case studies and expert input to help you avoid disaster, Develop Your Presentation Skills includes content to help you to deliver a presentation 'stripped bare' and to use new media to engage with your audience. This fully updated 5th edition now features even more practical exercises, useful templates and top tips to help you find your voice and use it with style; to inform, to persuade, to impress. From unpicking the original brief and understanding just what the audience wants, to facing your performance demons and constructing compelling content, you will keep your audience rapt with attention. The Creating Success series of books... Unlock vital skills, power up your performance and get ahead with the bestselling Creating Success series. Written by experts for new and aspiring managers and leaders, this million-selling collection of accessible and empowering guides will get you up to speed in no time. Packed with clever thinking, smart advice and the kind of winning techniques that really get results, you'll make fast progress, quickly reach your goals and create lasting success in your career"--
Keywords: Business presentations; Business communication